2021
DOI: 10.1002/vms3.565
|View full text |Cite
|
Sign up to set email alerts
|

Motivation‐based segmentation of game meat consumers: A look at the beliefs of food consumers during the COVID‐19 crisis in China

Abstract: Objectives This research aims to explore the factors motivate consumers to eat game meat during a multi‐state disease outbreak. Methods It proposes a segmentation of consumers based on their attitudes toward and reveals the consumers' food beliefs that motivate their actions. Three segments of game meat consumers were identified: identity seekers, health seekers, and taste seekers. Results A survey of the potential impact that the COVID‐19 cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…The study by Britwum, et al [ 18 ] on consumers’ perceptions regarding the desired attributes of organic produce found that consumers place the highest importance and confidence in the “free of growth hormones” and “free of synthetic pesticides” aspects of organic labeling. For Chinese consumers, purchasing organic agricultural products is motivated more by concerns regarding food safety and personal health and less by environmental protection [ 19 , 20 ]. Generally, institutional pesticide-free certification is less difficult and less costly to achieve than certified organic labeling.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Britwum, et al [ 18 ] on consumers’ perceptions regarding the desired attributes of organic produce found that consumers place the highest importance and confidence in the “free of growth hormones” and “free of synthetic pesticides” aspects of organic labeling. For Chinese consumers, purchasing organic agricultural products is motivated more by concerns regarding food safety and personal health and less by environmental protection [ 19 , 20 ]. Generally, institutional pesticide-free certification is less difficult and less costly to achieve than certified organic labeling.…”
Section: Introductionmentioning
confidence: 99%